2021
DOI: 10.7717/peerj.11974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a strawberry fermented beverage with potential health benefits

Abstract: Background Functional fermented beverages are popular worldwide due to their potential to promote health. Starter culture is the main determinant of the final quality and flavor of fermented beverages. The co-cultivation of lactic acid bacteria (LAB) and yeast makes a significant contribution to the safe flavor of fermented beverages. However, the research on the potential of antioxidant, antimicrobial, and anti-biofilm formation of strawberry fermented beverage obtained by combining the LAB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Considering the short harvest season, but also due to consumer preferences, strawberries are processed into various products, of which jams, purees, and juices are the most common [ 1 ]. For example, Zhao et al investigated the antioxidant and antibacterial potential of functional strawberry juice inoculated with a starter culture of lactic acid bacteria (LAB) and yeasts [ 8 ]. A similar methodology was used by Cataldo et al in their work in which strawberry juice was inoculated with Levilactobacillus brevis to study the immunomodulatory effect of gamma-aminobutyric acid on rodent cell cultures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the short harvest season, but also due to consumer preferences, strawberries are processed into various products, of which jams, purees, and juices are the most common [ 1 ]. For example, Zhao et al investigated the antioxidant and antibacterial potential of functional strawberry juice inoculated with a starter culture of lactic acid bacteria (LAB) and yeasts [ 8 ]. A similar methodology was used by Cataldo et al in their work in which strawberry juice was inoculated with Levilactobacillus brevis to study the immunomodulatory effect of gamma-aminobutyric acid on rodent cell cultures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of seven special glycosylated metabolites were screened for key differential metabolites (VIP > 1), namely 2′,4′,6′-trihydroxydihydrochalcone 2′-glucoside, delphinidin 3-sambubioside, pelargonidin-3-sophoroside, cyanidin 3-sambubioside 5-glucoside, luteolin 7-glucoside, peonidin-3-glucoside, and quercetin-4′-glucoside. Some fungi possess specific glycosyltransferases, which can transfer glycosidic bonds to designated metabolites, thereby increasing the diversity and stability of target metabolites ( 67 ) and improving their antioxidant capacities ( 68 ). In addition, studies have shown that the modification of glycosylation structure can improve the bioavailability of compounds like quercetin ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity was determined according to the previous method of our research group. The DPPH radical-scavenging activity, ABTS radical-scavenging activity, Hydroxyl radical-scavenging activity was determined according to Zhao et al ( 24 ). Fe 3+ reducing power was determined according to Tang et al ( 25 ).…”
Section: Methodsmentioning
confidence: 99%